INTERWEAVING MATHEMATICS AND HUMANITIES: FRACTALS AS A TOOL FOR ANALYZING SOCIOCULTURAL PHENOMENA - Nasibullov Kamil Iskhakovich (Western European Studies, 2024)
This article explores the significance of the fractal concept for social sciences and humanities, demonstrating how this mathematical concept has been applied in the analysis of complex sociocultural systems. It highlights the views of various scholars such as E.V. Nikolaeva, V.V. Tarasenko, and others, who have used fractal theory to study recurring cultural patterns, social interactions, and dynamic processes in society. The article shows how fractals help to understand the universality and complexity of natural forms and phenomena, and sheds light on their application in various fields - from biology and geology to physics, art, and architecture. Special attention is paid to the potential of fractal theory as an innovative method of research in social sciences and humanities, offering a new level of understanding and interpretation of social reality.
Keywords: fractal; social sciences and humanities